M1- and M2-Type Macrophage Responses Are Predictive of Adverse Outcomes in Human Atherosclerosis - de Gaetano, Monica; Crean, Daniel; Barry, Mary; Belton, Orina (Frontiers in Immunology, 2016)
Atherosclerosis is an inflammatory disease caused by endothelial injury, lipid deposition, and oxidative stress. This progressive disease can be converted into an acute clinical event by plaque rupture and thrombosis. In the context of atherosclerosis, the underlying cause of myocardial infarction and stroke, macrophages uniquely possess a dual functionality, regulating lipid accumulation and metabolism and sustaining the chronic inflammatory response, two of the most well-documented pathways associated with the pathogenesis of the disease. Macrophages are heterogeneous cell populations and it is hypothesized that, during the pathogenesis of atherosclerosis, macrophages in the developing plaque can switch from a pro-inflammatory (MΦ1) to an anti-inflammatory (MΦ2) phenotype and vice versa, depending on the microenvironment. The aim of this study was to identify changes in macrophage subpopulations in the progression of human atherosclerotic disease. Established atherosclerotic plaques from symptomatic and asymptomatic patients with existing coronary artery disease undergoing carotid endarterectomy were recruited to the study. Comprehensive histological and immunohistochemical analyses were performed to quantify the cellular content and macrophage subsets of atherosclerotic lesion. In parallel, expression of MΦ1 and MΦ2 macrophage markers were analyzed by real-time PCR and Western blot analysis. Gross analysis and histological staining demonstrated that symptomatic plaques presented greater hemorrhagic activity and the internal carotid was the most diseased segment, based on the predominant prevalence of fibrotic and necrotic tissue, calcifications, and hemorrhagic events. Immunohistochemical analysis showed that both MΦ1 and MΦ2 macrophages are present in human plaques. However, MΦ2 macrophages are localized to more stable locations within the lesion. Importantly, gene and protein expression analysis of MΦ1/MΦ2 markers evidenced that MΦ1 markers and Th1-associated cytokines are highly expressed in symptomatic plaques, whereas expression of the MΦ2 markers, mannose receptor (MR), and CD163 and Th2 cytokines are inversely related with disease progression. These data increase the understanding of atherosclerosis development, identifying the cellular content of lesions during disease progression, and characterizing macrophage subpopulation within human atherosclerotic plaques.